2022
DOI: 10.1039/d2sc01966c
|View full text |Cite
|
Sign up to set email alerts
|

Hemilabile MIC^N ligands allow oxidant-free Au(i)/Au(iii) arylation-lactonization of γ-alkenoic acids

Abstract: Oxidant-free Au-catalyzed reactions are emerging as a new synthetic tool for innovative organic transformations. Still, a deeper mechanistic understanding is needed for a rational design of these processes. Here we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…This shows that the second donor atom has an influence on both the barrier and the overall thermodynamics of the process. Indeed, the results mirror previous studies where oxidative addition requires a second donor to provide a small bite angle (here, ∠C NHC −Au−N=68.3° and 79.3° for the transition state and Au III product, respectively) [8–10, 14] …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This shows that the second donor atom has an influence on both the barrier and the overall thermodynamics of the process. Indeed, the results mirror previous studies where oxidative addition requires a second donor to provide a small bite angle (here, ∠C NHC −Au−N=68.3° and 79.3° for the transition state and Au III product, respectively) [8–10, 14] …”
Section: Resultssupporting
confidence: 88%
“…Bourissou and co‐workers reported Au I complexes modified with mesoionic carbene ligands bearing hemilabile N ‐groups (MIC^N); however, these systems were not effective for oxidative addition of iodobenzene [13] . Recently, Valdés, Guisado‐Barrios, Ribas and co‐workers reported two new (MIC^N)Au(I) complexes bearing hemilabile (pyridine or pyrimidine) groups [14] . The viability of oxidative addition of aryl iodides was demonstrated and applied to catalytic arylation‐lactonization reactions of γ‐alkenoic acids.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that Font et al reported studies towards a related Au(I)/Au(III) catalysed intramolecular addition of a carboxylic acid to form the corresponding lactone in modest yields using a bidentate C,N-ligand strategy in 2022. 37 Apart from heteroatom-based nucleophiles, pendant electron-rich arenes (33) have been utilized by Chintawar et al in 2020 as intramolecular nucleophiles towards the Au-catalysed Lewis acid alkene activation for the 1,2-alkene diarylation reaction in the synthesis of 34, Fig. 14A.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…It should be noted that Font et al reported studies towards a related Au( i )/Au( iii ) catalysed intramolecular addition of a carboxylic acid to form the corresponding lactone in modest yields using a bidentate C , N -ligand strategy in 2022. 37…”
Section: Applications In Synthesismentioning
confidence: 99%
“…Bourissou, Amgoune and co-workers reported that a Au­(I) center ligated by a rigid, narrow bite-angle carboranyl diphosphine ligand reacts with biphenylene to give a Au­(III) metallacycle ( vide infra ) . Related processes have been described using other LAu­(I) moieties, including L = NHC, cyclic (alkyl)­(amino)­carbene (CAAC), hemilabile P , N (MeDalPhos), and C , N -ligands . These auracycles are readily accessible compounds containing Au­(III)–C bonds, which we suspected might serve as excellent model systems for studying migratory insertion of CO (Scheme B).…”
mentioning
confidence: 99%